PENGARUH PENGETAHUAN, KEPERCAYAAN, DAN PROMOSI TERHADAP MINAT MENABUNG MAHASISWA DI BANK UMUM SYARIAH - Hanan Laily (2021)
The existence of Islamic commercial banks in Indonesia is currently very developed, but the national banking market share is still controlled by conventional commercial banks. This indicates that there is still little preference for saving in Islamic commercial banks. Therefore, the purpose of this study was to analyze the effect of knowledge, trust, and promotion on student interest in saving at Islamic commercial banks. Quantitative methods were used as research methods, with a sample of 200 students. Collecting data using a questionnaire via google form. Data were analyzed by multiple linear regression method. Hypothesis test using T test, F test, and coefficient of determination test. The results showed that the variables of knowledge, trust, and promotion had a simultaneous effect on interest in saving. Partially, the variables of knowledge, trust, and promotion show a positive and significant effect on interest in saving. From the results of the coefficient of determination test shows that the three independent variables affect the variable of interest in saving by 52%, the rest is influenced by other independent variables not examined. Based on the findings obtained in this study, Islamic commercial banks must continue to know what factors can influence student interest in saving at Islamic commercial banks apart from the three independent variables of this study. Keywords: interest in saving, islamic bank, knowledge, promotion, trust